Smart ID card For Females and Kids Security - S. Muthuselvan, S. Rajaprakash, Abhay Dev NS, Richu Michael, Vaishnavi vinod (International Journal of Advanced Science and Technology, 2020)
This is a Smart ID Card for school going children and office going women as all of us must have heard of a lot of cases of kidnapping and sexual abusement etc. among children and women and this can be a solution against many of those problems. The system would not be bulky so that it can be easily carried by children. It would help to the parent or guardian to find the location of the ward and they will get an alert on their phone while kidnapping happens. This can be done by pressing the button on the ID card that we fixed on it. The system consists of a processor, a GPS sensor, an nRF24L01 2.4 GHz Wireless Transceivers module and a SIM900A GSM/GPRS module. The GPS module giving us the raw data of latitude and longitude. So the basic system is already in place and the data collection has been successful. The major technique that we are using this project is RFID. We have tried to analyze the data that we obtained from the sensors. The GPS data was analyzed with the help of Google Map APIs. Keywords: Smart ID Card, Kids, GPS, GSM